Sinus venosus atrial septal defect: a rare cause of misplacement of pacemaker leads - Bodian, Malick (Dove Medical Press, 2013)
Routine implantation of pacemakers and implantable cardioverter defibrillators is not commonly associated with complications. However, in some cases we see misplacement of pacemaker leads which is most often related to the presence of underlying cardiac anomalies. We report the case of misplacement of a pacemaker lead into the left ventricle of a 56-year-old patient paced in VVI/R mode and with a tined type pacemaker lead because of a symptomatic complete atrioventricular block. Electrocardiogram showed a pacemaker-generated rhythm with a right bundle branch block pattern. Chest X-ray showed the pacemaker lead located relatively high in relation to the diaphragm. Echocardiography visualized the pacemaker lead in the left heart chambers (atrium and ventricle), hence confirming its aberrant course. Further, the defect causing its passage to the left heart chambers was a sinus venosus atrial septal defect. The patient reported no complication related to the misplacement of the lead. After a brief period of oral anticoagulation, the lead was inserted into the right ventricle by percutaneous technique.